2019
DOI: 10.1186/s40359-019-0322-z
|View full text |Cite
|
Sign up to set email alerts
|

Does the discrepancy between implicit and explicit attitudes moderate the relationships between explicit attitude and (intention to) being physically active?

Abstract: Background Explicit attitudes as well as implicit attitudes have been shown to be associated with physical activity (PA). These two types of attitudes can, however, be discrepant towards the same object or behavior. This study investigated whether there is a discrepancy between explicit and implicit attitudes (IED) regarding physical activity (PA), and whether IED moderates the relationship between explicit attitude and PA, and explicit attitude and PA intention. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 80 publications
(125 reference statements)
7
15
0
Order By: Relevance
“…An additional finding of the present study was that IED was related to behavior at all three measurement points, which was also the case in former studies [29,30,[32][33][34]69]. In the current study, the relationship was negative.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…An additional finding of the present study was that IED was related to behavior at all three measurement points, which was also the case in former studies [29,30,[32][33][34]69]. In the current study, the relationship was negative.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, the non-acceptance of dissonance had a positive and thereby desirable effect on the intention to reduce RMC. Future studies should investigate in which contexts dissonance results in healthy behaviors, as it was the case in the present study, and in which contexts dissonance results in rather unhealthy behaviors, as demonstrated in former studies [32][33][34]. Shedding light on these questions would allow interventions to consciously induce dissonance in order to achieve certain behavior changes.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…One study found positive automatic evaluations between exercise and social/appearance outcomes in adolescents but no similar relationship between exercise and desirable or undesirable health outcomes (22). Social desirability is another possible moderator to consider within the exercise domain (7,23). It is possible that explicit evaluations of exercise among youth are in uenced by social desirability althoguh several reserachers have found that social desirability was not a signi cant moderator among adults(6, 7).…”
Section: Introductionmentioning
confidence: 99%